Exploring the role of the nurse educator, at a nursing education institution in Cape Town, on preparing undergraduate nursing students to provide compassionate nursing care - Lotz, Claudette (Stellenbosch : Stellenbosch University, 2024)
Thesis (MNur)--Stellenbosch University, 2024.